FACTORS DETERMINING SUCCESS OF TOURIST PRODUCTS IN MAŁOPOLSKA - Lemanowicz, Marzena; Puciata, Ewa (Acta Scientiarum Polonorum. Oeconomia, 2010)
The paper presents results of research on factors determining a success of tourist products in Małopolska. Special attention was paid to tourist attractiveness, tourist information, tourist management in the region as well as promotion activities. These issues were recognized by the authors as the key elements, which can infl uence on the success of tourist products. The conducted research involved evaluation of tourist attractiveness of the region, identification of factors deciding on an arrival in Małopolska as well as evaluation of knowledge of promotional campaigns organized by the regional authorities.